Pembelajaran Tematik dan Integratif di Sekolah Dasar - Jakiyah Jakiyah (Proceedings Series of Educational Studies, 2023)
Abstract: This paper aims to encourage students to be able to make observations, ask questions, reason, and communicate (report), what students get in learning and to integrate various subject matter in one particular theme or topic, so that students can learn holistically and integrated. Thematic and integrative learning is also able to develop students' ability to understand the relationship between various aspects of learning and its application in everyday life. This writing uses the literature study method, this method involves collecting, analyzing, and synthesizing information from written sources such as books, journals, articles, and other related sources to gain a deeper understanding of thematic and integrative learning. Objects in thematic and integrative learning are topics or themes that are the main focus of learning. These objects are usually topics related to everyday life such as culture, art, social and natural phenomena. This writing is intended to describe the concept and implementation of integrative thematic learning in elementary schools. An integrative thematic approach is learning that integrates various abilities from various subjects into various themes.Keywords: Learning, thematic and integrativeAbstrak: Tulisan ini bertujuan untuk mendorong peserta didik untuk mampu melakukan observasi, bertanya, bernalar, dan mengkomunikasikan (mempresentasikan), apa yang peserta didik dapat dalam pembelajaran dan untuk mengintegrasikan berbagai materi pelajaran dalam satu tema atau topik tertentu, sehingga peserta didik dapat belajar secara holistik dan terintegrasi. Pembelajaran tematik dan integratif juga mampu mengembangkan kemampuan siswa dalam memahami hubungan antara berbagai aspek pelajaran dan aplikasinya dalam kehidupan sehari-hari. Penulisan ini menggunakan metode studi literatur, metode ini melibatkan pengumpulan, analisis, dan sintesis informasi dari sumber-sumber tertulis seperti buku, jurnal, artikel, dan sumber-sumber terkait lainnya untuk mendapatkan pemahaman yang lebih dalam tentang pembelajaran tematik dan integratif. Objek dalam pembelajaran tematik dan integratif adalah topik atau tema yang dijadikan fokus utama dalam pembelajaran. Objek ini biasanya merupakan topik yang terkait dengan kehidupan seharihari seperti budaya, seni, sosial dan fenomena alam. Penulisan ini ditujukan untuk mendeskripsikan konsep dan implementasi pembelajaran tematik integratif di sekolah dasar. Pendekatan tematik integratif merupakan pembelajaran yang mengintegrasikan berbagai kemampuan dari berbagai mata pelajaran kedalam berbagai tema.Kata kunci: Pembelajaran, tematik dan integratif